1998
DOI: 10.1038/sj.bjc.6690015
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of cisplatin in human head and neck cancer: correlation between platinum content, DNA adduct levels and drug sensitivity in vitro and in vivo

Abstract: Summary Total platinum contents and cisplatin-DNA adduct levels were determined in vivo in xenografted tumour tissues in mice and in vitro in cultured tumour cells of head and neck squamous cell carcinoma (HNSCC), and correlated with sensitivity to cisplatin. In vivo, a panel of five HNSCC tumour lines growing as xenografts in nude mice was used. In vitro, the panel consisted of five HNSCC cell lines, of which four had an in vivo equivalent. Sensitivity to cisplatin varied three-to sevenfold among cell lines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 26 publications
1
19
1
Order By: Relevance
“…In contrast to our study, Welters et al (40) found significant correlations between platinum-DNA adducts and tumor response in xenografted tumor tissues and in cultured tumor cells of head and neck squamous cell cancer. Other investigators have explored the relationship between platinum-DNA adduct formation in peripheral blood leukocytes and clinical response in patients undergoing chemotherapy.…”
Section: Discussioncontrasting
confidence: 52%
“…In contrast to our study, Welters et al (40) found significant correlations between platinum-DNA adducts and tumor response in xenografted tumor tissues and in cultured tumor cells of head and neck squamous cell cancer. Other investigators have explored the relationship between platinum-DNA adduct formation in peripheral blood leukocytes and clinical response in patients undergoing chemotherapy.…”
Section: Discussioncontrasting
confidence: 52%
“…Whether the accumulation of Pt in the kidney relates to renal toxicity remains unknown; 27, 28 it has been reported that the Pt-DNA adduct but not the total tissue Pt levels could provide a more useful correlation with the renal damage induced by Pt. 29 …”
Section: Resultsmentioning
confidence: 99%
“…This dose is about 2 times higher than the maximum intravenous dose that can be tolerated without STS protection and therefore probably yields higher dose intensity at the targeted tumor site, provided that the molar STS/CDDP ratio in the tumor remains low as compared with that in plasma. This precondition is particularly important during the first 30 to 60 minutes of the CDDP tumor exposure because cisplatin deoxyribonucleic acid adducts are mainly formed during this time 12 , 13 , 14 . Use of the IA cisplatin approach in more than 300 patients with squamous cell carcinoma of the oral cavity provided good clinical results with respect to response and toxicity 1 , 2 , 15 , 16 …”
mentioning
confidence: 99%